Udah Cebol, Bantet Pula Aku: Lexical Cohesion on Body Shaming in IbuHamil.com Discussion Forum (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
Women contribute almost half of the total internet users in Indonesia and millennial mothers are a significant group of internet users, especially social media. This makes the millennial mother group vulnerable to crime in the digital space. One form of crime is body shaming which is part of mom-shaming. In this study, we investigate body shaming from the perspective of Discourse Analysis using Halliday and Hasan's classification on lexical cohesion. We focus on three categories in lexical cohesion, which are repetition, synonymy, and antonymy to illustrate lexical cohesion in IbuHamil.com’s discussion forum. Body shaming discussed in the article sources from a thread in Ngobrol Apa Saja forum in IbuHamil.com. The thread discussing body shaming experience receives 37 responses in 18 days. In terms of lexical cohesion, the data display 300 words in repetition with 28 inflected words, 38 words in synonymy, and 16 words in antonymy. There are some typical words in illustrating physical features in body shaming, which mainly highlight weight, height, and attempts to achieve an ideal body mass index. The discussion forum also demonstrates the frequent use of contraction which characterizes the internet chat room communication. Additionally, users' responses express empathy and support to the topic starter. The users also propose advice on handling body shaming and how to avoid it in the future.